2021
DOI: 10.3390/ijms221910697
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Metabolic Insights into Anthocyanin Biosynthesis for Leaf Color Change in Chokecherry (Padus virginiana)

Abstract: Chokecherry (Padus virginiana L.) is an important landscaping tree with high ornamental value because of its colorful purplish-red leaves (PRL). The quantifications of anthocyanins and the mechanisms of leaf color change in this species remain unknown. The potential biosynthetic and regulatory mechanisms and the accumulation patterns of anthocyanins in P. virginiana that determine three leaf colors were investigated by combined analysis of the transcriptome and the metabolome. The difference of chlorophyll, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Previous studies have demonstrated that the formation of leaf color in plants is mainly regulated by anthocyanins, which could influence pigmentation and relative gene expression ( Jia et al, 2020 ; Qiu et al, 2020 ). It has been shown that six anthocyanidins, pelargonidin, malvidin, peonidin, cyanidin, delphinidin, and petunidin, are common in leaf/fruit color changes ( Sulc et al, 2017 ; Li et al, 2021c ). In our study, 14 differential anthocyanins were identified in the leaves of A. pseudosieboldianum and mainly contained three categories of pelargonidin, cyanidin and peonidin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the formation of leaf color in plants is mainly regulated by anthocyanins, which could influence pigmentation and relative gene expression ( Jia et al, 2020 ; Qiu et al, 2020 ). It has been shown that six anthocyanidins, pelargonidin, malvidin, peonidin, cyanidin, delphinidin, and petunidin, are common in leaf/fruit color changes ( Sulc et al, 2017 ; Li et al, 2021c ). In our study, 14 differential anthocyanins were identified in the leaves of A. pseudosieboldianum and mainly contained three categories of pelargonidin, cyanidin and peonidin.…”
Section: Discussionmentioning
confidence: 99%
“…Freeze-dried leaves were used for extracting chlorophyll and carotenoids referring to the method described by Li et al [ 29 ]. The samples of non-heading Chinese cabbage (0.2 g) were cultured in 5 mL of 96% ethanol ( v / v ) for 24 h at 24 ◦C, then vortexed for 30 s after culturing for 12 h in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA extraction and library construction were carried out according to Li et al (2021) . The libraries were sequenced on the Illumina HiSeq platform with an average reading length of 125 bp/150 bp.…”
Section: Methodsmentioning
confidence: 99%
“…PtActin (amplification primers were F: 5′-AAT​ACC​CCA​TTG​AGC​ACG​G-3′, R: 5′- ACT​CAC​ACC​ATC​ACC​AGA​ATC-3′) were selected as an internal reference gene. The amplification system and procedure were carried out according to Li et al (2021) . The relative expression level of genes was calculated using the 2 −∆∆CT method ( Livak and Schmittgen.…”
Section: Methodsmentioning
confidence: 99%